Development and Scaling of Sustainable Feeds for Resilient Aquatic Food Systems in Sub-Saharan Africa: Life Cycle Assessment - Ndebele-Murisa, Mzime; Mubaya, Chipo; Kapute, Fanuel; Samundengo, Angela; Yossa, Rodrigue (WorldFish, 2024)
An LCA can help identify opportunities to improve the environmental performance of products at various points in their life cycle. It addresses the environmental aspect and its potential impact, such as the use of resources and the environmental consequences of releases, throughout a product’s life cycle—from acquiring raw materials through to production, use, end-of-life treatment, recycling and final disposal, also known as the “cradle-to-grave” concept. Integrating climate and environmental considerations into fish feed life cycles broadens our understanding of aquaculture’s GHG emissions and potential mitigation in managing feeds and feeding.